LEGAL CONSEQUENCES OF INSIDER TRADING IN A SHARE TRANSACTION BY PT PERUSAHAAN GAS NEGARA TBK IN INDONESIA - Fany Aprillia Regita Cahyani; Durratun Afifah; Sumriyah (Media Inovasi Pendidikan dan Publikasi, 2023)
In carrying out capital market activities, all parties in a public offering are obliged to fulfill and pay attention to the principle of transparency. There was a violation in the capital market that was committed by PT Perusahaan Gas Negara. This can be seen from the 23.36 percent drop in PNG's share price on the JSE from Rp. 9,650 on 11 January 2006 to Rp. 7,400 per share on January 12, 2007. The Capital Market and Financial Institution Supervisory Agency (Bapepam-LK) imposed administrative sanctions in the form of fines against 9 employees and former PT. PGN is involved in the insider trading case.